SHARIA-COMPLIANT INVESTMENT FUNDS IN THE U.S. MARKET: NAVIGATING SEC REGULATIONS AND ETHICAL FINANCE DEMANDS - Jessica Anderson; William Lee; Jennifer Taylor (Sharia Oikonomia Law Journal, 2025)
The rising demand for ethical and faith-based investment products in the United States has prompted increased interest in Sharia-compliant investment funds. These funds seek to align financial returns with Islamic principles, including the prohibition of interest (riba), avoidance of excessive uncertainty (gharar), and investment in halal sectors. However, integrating such models within the U.S. financial system presents regulatory challenges, particularly under the oversight of the Securities and Exchange Commission (SEC). This study examines how Sharia-compliant investment funds navigate U.S. regulatory frameworks while maintaining theological legitimacy and investor confidence. Utilizing a qualitative legal research methodology, the study analyzes SEC rules on mutual funds and ETFs, including disclosure, diversification, and fiduciary obligations, alongside Shariah governance standards issued by AAOIFI and other global Islamic finance authorities. Interviews with fund managers, legal counsel, and Shariah advisors provide practical insights. Findings indicate that although structural compatibility is possible, regulatory ambiguities around Shariah governance, purification processes, and ethical screening create operational tensions. The study concludes that successful integration requires interpretive flexibility, SEC engagement, and investor education to ensure both compliance and religious authenticity. The research contributes to broader discussions on financial inclusion, ethical finance, and legal pluralism in global markets.